2006
DOI: 10.1074/jbc.m513297200
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Apoptosis by Cyclophilin D via Stabilization of Hexokinase II Mitochondrial Binding in Cancer Cells

Abstract: The permeability transition pore is involved in the mitochondrial pathway of apoptosis. Cyclophilin D, a pore component, has catalytic activity as a peptidyl prolyl cis, trans-isomerase (PPIase), which is essential to the pore opening. It has been reported that cyclophilin D overexpression suppresses apoptosis in cancer cells. To clarify the mechanism of this effect, we generated glioma cells overexpressing wild-type or a PPIase-deficient mutant of cyclophilin D. Interestingly, we found that the PPIase-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 37 publications
6
97
0
2
Order By: Relevance
“…18 Interestingly, Cyp D, which genetic evidence shows to be critical for PT-pore induction, 19,20 was recently reported to suppress apoptosis via stabilization of HK-II binding to mitochondria. 26 While our data demonstrate that mitochondrial HK-II is a key inhibitor of PT-pore (Ca 2 þ -mediated and Cs-A sensitive) induced cytochrome c release, and previous papers show that overexpression of HK is protective against stress. 37,38 Much additional study will be required to elucidate the mechanisms by which HK-II keeps PT pore opening in check.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…18 Interestingly, Cyp D, which genetic evidence shows to be critical for PT-pore induction, 19,20 was recently reported to suppress apoptosis via stabilization of HK-II binding to mitochondria. 26 While our data demonstrate that mitochondrial HK-II is a key inhibitor of PT-pore (Ca 2 þ -mediated and Cs-A sensitive) induced cytochrome c release, and previous papers show that overexpression of HK is protective against stress. 37,38 Much additional study will be required to elucidate the mechanisms by which HK-II keeps PT pore opening in check.…”
Section: Discussionsupporting
confidence: 45%
“…13,22 A role for hexokinase in mitochondrial protection was recently reported. [22][23][24][25][26] Interestingly the ability of Akt to protect against cytochrome c release and apoptosis in fibroblasts was shown to be decreased by HK-II dissociation from mitochondria. 27 The question of whether hexokinase is a mediator of cell survival in the heart has not been examined, although HK-II is abundantly expressed in cardiomyocytes.…”
mentioning
confidence: 99%
“…100,101 Interestingly, CyPD activity stabilizes mitoHK-II binding and forced dissociation of mitoHK-II leads to disruption of CyPD binding to ANT, suggesting a functional link between a stimulatory (CyPD) and an inhibitory (HK-II) molecule of the mPTP. 96,[102][103][104][105] It seems likely that the interaction between HK-II and CyPD is mediated by the previously mentioned VDAC/ANT interaction. 106,107 However, genetic evidence revealed that neither VDAC nor ANT is the main pore-forming component [108][109][110][111] and thus it is still not clear whether the indirect interaction of HK-II with CyPD plays a direct role in regulation of the mPTP.…”
Section: Pro-survival Effect Of Hk-iimentioning
confidence: 97%
“…Fast and massive ATP depletion by jasmonate-induced hexokinase detachment fits with the fact that other agents known to detach mitochondrial hexokinase also induce ATP depletion preceding the decrease in cell viability (Miccoli et al, 1998;Machida et al, 2006).…”
Section: Discussionmentioning
confidence: 99%